Penggunaan lembar kerja peserta didik untuk meningkatkan keterampilan mengolah informasi sejarah siswa (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2022)
This research is based on several problems associated with a lack of information processing skills in history learning students based on pre-observation in class X IPS 3 SMA Laboratorium Universitas Pendidikan Indonesia. The purpose of this research is that by using Student Worksheet, the students can perform their skill of historical information processing. This research use Class Action Research as a research method with Kemmis & Mc Tagaart’s research design, which has four activities in every cycle, planning, acting, observing, and reflection. They are based on the result of research. In the first cycle, the student’s skill in historical information processing still needs to improve. Still, many students use only one source in their worksheets and can only write conclusions within the minimum usage of words. In the second cycle, the rate of this skill increased quite well. The student’s scores in information searching, selecting, and assessing are pretty good. Interpretation is perfect for information, but concluding still needs to be better. Next, in the third cycle, the student’s skills increased significantly. In this cycle, the students using two or more sources for their work can develop their argument well, interpretating information chronologically, and write the conclusion using their own words. From this result, applying a non-structural Student Worksheet can be an alternative solution for teachers to develop information-processing-based learning.
Keywords: Historical Learning; Information Proceessing Skill; Student Worksheet